Implementasi Teknologi Face Recognition dalam Meningkatkan Efisiensi Proses Boarding Penumpang di PT Kereta Api Indonesia - Annisa Nurinsani; Firman Yudhanegara (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Advances in digital technology are driving the transformation of public transportation services, one example being the implementation of face recognition boarding gate at PT Kereta Api Indonesia (Persero). This study aims to analyze the implementation of face recognition boarding gate technology in improving the efficiency of the passenger boarding process at Kiaracondong Station, as well as to identify the challenges encountered in its implementation. This study employs a descriptive qualitative approach using a case study method through participatory observation and documentation techniques. The results indicate that the use of face recognition boarding gate improves the efficiency of the boarding process, reducing the average time to 2-4 seconds per passenger compared to manual boarding, which takes approximately 6-10 seconds per passenger, thereby increasing service capacity and reducing queues. Analysis using the Technology Acceptance Model (TAM) indicates that user acceptance is influenced by perceptions of the system’s benefits and ease of use. Identified challenges include verification failures due to face coverings, data mismatches, and technical glitches in the devices. From an operational management perspective, this technology contributes to workflow optimization and service effectiveness, but requires ongoing system maintenance support, infrastructure strengthening, and user education.